Anísio Teixeira: a poesia da ação - Clarice Nunes (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
The opening conference of the twentieth third annual meeting of ANPEd had as a central theme Education is not a Privilege: the centennial of Anísio Teixeira. Honouring this Brazilian educator, the conference remembered his life performance under three breaking points located in time at the end of the twenties, in 1935 and in 1964. Under the light of his career, the evaluation of his work makes us think about the contemporary problems of education in our society especially the globalization of economy, the institutional violence and the challenges of the educational research.